The Perception of the Elderly in LKS-LU Pangesti Lawang Towards Death: A Phenomenological Analysis - Yafet Pradikatama Prihanto; Achmad Syukkur; Mochamad Ali Sodikin (Indonesian Journal of Global Health Research, 2026)
Death is the final process of human life. In the course of a typical human lifespan, old age represents the final stage before death. The elderly’s perception of death varies significantly among individuals and is influenced by various factors, including previous experiences of loss, closeness to significant others, and living arrangements—whether residing with family or in a nursing home. This study aims to explore and analyze the perceptions of older adults regarding death at the Social Welfare Institution (LKS) LU Pangesti Lawang. Death is a topic often avoided in conversation, yet it is essential to understand, particularly among elderly individuals living in institutional settings. As a group that is inherently closer to the end of life, the elderly's perception of death may greatly affect their psychological well-being. This research employed a qualitative method using a phenomenological approach to understand the subjective experiences of older adults in interpreting death. The participants consisted of seven elderly individuals residing in LKS LU Pangesti Lawang, selected through purposive sampling. Data were collected through in-depth interviews and observation, then analyzed using thematic analysis to identify the main themes related to their perceptions of death. The findings revealed six main themes that address the specific objectives of the study: Emotional unrest, End of life, Changes in perspective, Hopes for life after death, Frailty, Death as destiny Each of these six themes comprises several sub-themes, which were derived from categories and key phrases in participants’ responses to the research questions.